2008
DOI: 10.3102/0002831208319722
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Spelling in the Primary Grades: A National Survey of Instructional Practices and Adaptations

Abstract: Primary grade teachers randomly selected from across the United Sates completed a survey (N = 168) that examined their instructional practices in spelling and the types of adaptations they made for struggling spellers. Almost every single teacher surveyed reported teaching spelling, and the vast majority of respondents implemented a complex and multifaceted instructional program that applied a variety of research-supported procedures. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 32 publications
4
85
2
4
Order By: Relevance
“…Individual children with weak spelling skills should be identified and provided appropriate instruction to change their standing relative to age or grade peers in spelling and prevent failure in writing tasks, as this may lead to avoiding the difficult task of spelling and the associated composing. S. Graham et al (2008) surveyed a representative sample of teachers in the United States and found that only about a third had adopted a systematic spelling program. Future research should evaluate whether providing a systematic, explicit, evidence-based spelling program beginning in first grade optimizes the spelling achievement of struggling, average, and superior spellers from the beginning and all along their journey toward skilled writing and reading, so they not only become expert writers, readers, writing readers, and reading writers but also enjoy written language.…”
Section: New Knowledge About Spellingmentioning
confidence: 99%
“…Individual children with weak spelling skills should be identified and provided appropriate instruction to change their standing relative to age or grade peers in spelling and prevent failure in writing tasks, as this may lead to avoiding the difficult task of spelling and the associated composing. S. Graham et al (2008) surveyed a representative sample of teachers in the United States and found that only about a third had adopted a systematic spelling program. Future research should evaluate whether providing a systematic, explicit, evidence-based spelling program beginning in first grade optimizes the spelling achievement of struggling, average, and superior spellers from the beginning and all along their journey toward skilled writing and reading, so they not only become expert writers, readers, writing readers, and reading writers but also enjoy written language.…”
Section: New Knowledge About Spellingmentioning
confidence: 99%
“…However, teachers report using a variety of spelling activities (Graham et al 2008;McNeill and Kirk 2014) and many intervention studies report using multi-component spelling instruction (e.g., Berninger et al 2002;Graham et al 2002;Kirk and Gillon 2009). Aside from the instructional methods we investigated, other common methods include alphabetizing, writing-saying, finding the missing letter, unscrambling the letters, word searches, and dictionary work.…”
Section: Spelling Accuracy (%)mentioning
confidence: 99%
“…3 To clarify, it is not argued that reading and whole language activities have no impact on spelling acquisition. According to the research, such activities can contribute to spelling development, but on their own they are, for many children, insufficient to develop understanding of how the spelling system works (Graham et al, 2008;Hammond, 2004;Westwood, 2005Westwood, , 2008a. 4 As one reviewer pointed out, this represents a return to what was almost always the case prior to the 1970s.…”
Section: Endnotesmentioning
confidence: 99%
“…Neither rote visual memorisation or the incidental learning approach lead to the automaticity of recall needed for both reading and writing (Schlagal, 2002;Templeton, 1991;Templeton & Morris, 1999). 3 What is required for automaticity of recall is spelling instruction that is explicit and systematic, focusing on exploring patterns that can be detected in the sound, structure, and meaning features of words, and thus reinforcing and consolidating children's understanding of how the spelling system works (Graham et al, 2008;Hammond, 2004;Schlagal, 1992;Westwood, 2005Westwood, , 2008a.…”
mentioning
confidence: 99%